La función del órgano de control de una sociedad cooperativa europea domiciliada en España - Fuentes Naharro , Mónica (REVESCO. Revista de Estudios Cooperativos, 2009)
The legal statute contained in Regulation (EC) 1435/2003 on the European Cooperative (SCE), following its precedent and model, the Regulation 2157/2001 on the European Company, has incorporated the possibility that the SCE, by means of its by-laws, can choose between two models of management: the two-tier system (virtually unknown in our national cooperative law) or the one-tier system. Indeed, while the one-tier system is well known and has been subject to multiple and meritorious work by our doctrine, we considered suitable to focus our efforts on the so-called “monitoring body”, which is the true "distinguishing mark" of this two-tier system. However, addressing all the monitoring body’s legal regime would exceed by far the objective of this conference. Thus, we shall confine ourselves, in essence, to make an analytical and, sometimes, critical approach to the functions of this body with the other body of this two-tier system, in charge of the effective administration of society (the socalled management body or simply Management). Not a few difficulties we will have to face on this task, almost all of them related to interpretation and adaptation problems that will arise when implementing the European Regulation within the existing Spanish rules on cooperatives, through the articulation of those specific provisions which are needed to adapt our legislation to the new legal type and, more specifically, the new two-tier system of management.
Keywords: Two-tier Board System; Supervisory Board; Management; Cooperative